Conflicting intersexual mate choices maintain interspecific sexual interactions. Issue 2 (4th June 2015) - Takakura, Koh‐Ichi; Nishida, Takayoshi; Iwao, Keisuke
Abstract: Reproductive interference, interspecific sexual interactions that affect reproductive success, is found in various taxa and has been considered as a fundamental source of reproductive character displacement (RCD). Once RCD has occurred, persistent interspecific sexual interactions between species pairs are expected to diminish. However, reproductive interference has been reported from some species pairs that sympatrically coexist. Thus, the question arises, can reproductive interference persist even after RCD? We modeled the evolutionary dynamics of signal traits and mate recognition that determine whether interspecific sexual interactions occur. Our models incorporate male decision making based on the recognition of signal traits, whereas most previous models incorporate only female decision making in mate selection. Our models predict the following: (1) even when male decision making is incorporated, males remain promiscuous; (2) nevertheless, the frequency of interspecific mating is maintained at a low level after trait divergence; (3) the rarity of interspecific mating is due to strict female mate recognition and the consequent refusal of interspecific courtship by females; and (4) the frequency of interspecific mating becomes higher as the cost to females of refusing interspecific courtship increases. These predictions are consistent with empirical observations that males of some species engage in infrequent heterospecific mating. Thus, our models predict that reproductive interference can persist even after RCD occurred.